Flâneur in the sandbox – experiencing the navigable space in computer games - Chojnacki, Marcin M. (Replay. The Polish Journal of Game Studies, 2014)
Spatiality of computer games is one of the most important features that affect the way they are received by the players. That is why it becomes a common subject of discussion among researchers involved in analyzing the properties of the medium. In this essay I will describe some aspects that may affect the player’s experience of being in an interactive environment. I will consider if it is possible to find joy in navigation through open world games and try to answer the question of whether the definition of flâneur can be applied to characterize the role of the player focused on strolling along the game world.